Partisipasi Jemaat Dalam Bulan Budaya Dan Implikasinya Terhadap Pelestarian Budaya Lokal di Kalangan Jemaat Gmit Bukit Kalvari Nunuteta - Marwela R. Seo; Yerliani Boymau; Yosep Sudarso; Maya Djawa (Badan Penerbit STIEPARI Press, 2024)
This study aims to describe the forms of congregation participation in the Cultural Month celebration at GMIT Bukit Kalvari Nunuteta and its implications for the preservation of local culture. In the context of globalization that threatens the existence of traditional cultures, the church is viewed as a key agent in sustaining the cultural identity of its members. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and documentation. The findings reveal that congregational participation spans all stages of activity—from planning, implementation, benefit utilization, to evaluation. This involvement is not merely symbolic but active and spiritual, reflecting the integration of faith and culture in church life. The Cultural Month serves not only as a means of inculturation but also strengthens the collective awareness of the congregation regarding the importance of transmitting local cultural values across generations. The study recommends reinforcing culturally based church ministry strategies to support the sustainable preservation of local heritage.